Manajemen Peminjaman Kunci Menggunakan Fingerprint Pada Laboratorium Komputer Jurusan Teknik Informatika - Fendi Hermawanto; Arif Agus Fajar Riyanto; Nur Cholik Hasyim (Jurnal Pengelolaan Laboratorium Pendidikan, 2021)
The Informatics Engineering Department has laboratory facilities used in the teaching and learning process, including the Tempat Uji Kompetensi(TUK) Laboratory, Desain, Hardware, Program 1, Program 2, Database, Nirkabel, and Multimedia. The purpose of this research is to create an automatic key lending system with fingerprint authentication that can be done independently without the supervision of a technician / PLP. This study uses the Research and Development (R&D) method. The stages of the R&D method are potentials and problems, system design, manufacture and improvement of tools, data collection, tool accuracy testing, results and discussion, and conclusions. Starting from the potential and problem stages which is carried out by analyzing problems that occur in the previous loan system, followed by system design which is divided into software and hardware design. The next stage is manufacturing and refinement, starting with the creation of a key chain holder, key chain, PCB, microcontroller programming and building a key lending website. Data were collected by interview method. Measured the average percentage of successful loans which resulted in a percentage of 81%. The result of this research is the creation of an automatic key lending system with fingerprint authentication at the Computer Laboratory of the Department of Informatics. This research has solved the problem of borrowing a manual key previously which had to be supervised by a technician / PLP.